2010
DOI: 10.3133/ofr20101229
|View full text |Cite
|
Sign up to set email alerts
|

Unintended consequences of biofuels production?The effects of large-scale crop conversion on water quality and quantity

Abstract: I n the search for renewable fuel alternatives, biofuels have gained strong political momentum. In the last decade, extensive mandates, policies, and subsidies have been adopted to foster the development of a biofuels industry in the United States. The Biofuels Initiative in the Mississippi Delta resulted in a 47-percent decrease in cotton acreage with a concurrent 288-percent increase in corn acreage in 2007. Because corn uses 80 percent more water for irrigation than cotton, and more nitrogen fertilizer is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…Out study indicated that this land management change could enhance the SOC sequestration, mitigating anthropogenic CO 2 emissions (see Sections 3.2 and 3.3). However, the intensified corn growth would decrease the water availability due to the higher water consumption by corn and likely worsen the hypoxia in the Gulf of Mexico because of the higher nutrient loads resulting from the higher fertilization rate for corn when compared to other small grains (e.g., soybean) [ CWIBP , 2008; Thomas et al ., ; Welch et al ., ; Wu et al ., ]. Therefore, increasing corn growth frequency is still a double‐edged sword strategy in terms of environmental protection, causing conflict in CO 2 mitigation and water resources protection.…”
Section: Resultsmentioning
confidence: 99%
“…Out study indicated that this land management change could enhance the SOC sequestration, mitigating anthropogenic CO 2 emissions (see Sections 3.2 and 3.3). However, the intensified corn growth would decrease the water availability due to the higher water consumption by corn and likely worsen the hypoxia in the Gulf of Mexico because of the higher nutrient loads resulting from the higher fertilization rate for corn when compared to other small grains (e.g., soybean) [ CWIBP , 2008; Thomas et al ., ; Welch et al ., ; Wu et al ., ]. Therefore, increasing corn growth frequency is still a double‐edged sword strategy in terms of environmental protection, causing conflict in CO 2 mitigation and water resources protection.…”
Section: Resultsmentioning
confidence: 99%
“…The simulated environmental impacts of the case study are generally consistent with other published studies (CWIBP, ; Simpson et al ., ; Thomas et al ., ; Baskaran et al ., ; Ng et al ., ; Vanloocke et al ., ; Welch et al ., ; Love & Nejadhashemi, ). However, this study further addresses the connections between biofuel production and environmental cost (in terms of water quality) by elaborating on the relationship of biomass production and the resulting nitrogen load against switchgrass planting acreage and locations (Figs ).…”
Section: Resultsmentioning
confidence: 99%
“…Other biofuel LUC issues and concerns, in addition to increased GHG emissions, are higher or more volatile food prices, which hurt the poor (FAO, 2008;FAO et al, 2011); conversion of high biodiversity areas; overuse or degradation of water or land resources; damage to important ecosystem services (Koh and Wilcove, 2008;Donner and Kucharik, 2008;Welch et al, 2010); and disruption of land ownership or other social patterns (Toulmin, 2009). LUC impacts can also be positive, depending on location and management practices: biofuel LUC can improve resource productivity, sequester carbon, and provide additional income for rural populations (Tilman et al, 2009;Berndes et al, 2010).…”
Section: Introductionmentioning
confidence: 98%